JomJalan ! Planner; Mobile Application for Malaysia Tourism Industry - Fatimah Zahrah, Abdul Ghani
The tourism industry is one of the major industries in Malaysia where it is one of the major sources of the country's economy. Traveling activities that have various categories for tourists enjoy are also the main reasons for this proposed project. Although there are many travel mobile applications, it is not effective in helping to ease the user's activities. Therefore, the ultimate goal is to develop JomJalan! This planner is to help users in organizing their travels while they are on vacation. By using the mobile application as a mediator for the user to facilitate because the mobile is a suitable medium to be used. Among the features such as booking tickets online, recording plans and writing journals to share views can help travelers organize their travel effectively.